Modulation of major histocompatibility complex (MHC) class i heavy chain gene expression by naringenin in cells that express human papillomavirus (HPV) E6 and E7 genes - Yusof, Rohana; Yim, Yong Hoi; Mohd, Mustafa Ali; Blair, G Eric (2004)
This study describes the effect of Naringenin on major histocompatibility complex (MHC) class I heavy chain gene expression in the presence of low risk or high risk Human Papillomavirus (HPV) E6 and E7 genes. Northern blot analysis showed that, in the presence of Naringenin, steady-state levels of MHC class I heavy chain mRNA transcripts were elevated in rat fibroblast (3Y1) cells. In transient expression assays of MHC class I heavy chain (H-2Kb) promoter activity, it was observed that there was a down-regulation of MHC class I promoter activity in 3Y1 cells co-transfected with either high risk HPV 16 E6 and E7 or low risk HPV 6 E6 and E7 expression plasmids. Treatment of control 3Y1 cells and cells co-transfected with high or low risk HPV E6 and E7 plasmids with 300Âµg/ml of Naringenin for 24 hours led to an increase in H-2Kb-driven CAT (chloramphenicol acetyl transferase) reporter gene activity. Thus, Naringenin retained the ability to increase H-2Kb promoter activity in the presence of either E6 or E7 expression constructs, indicating that Naringenin can over-ride the transcriptional repressor effects of HPV oncoproteins and may therefore have some potential immunostimulatory properties in HPV-associated malignancy.